Numerical analysis of multipurpose shell-tube-heat exchanger withal stylized geometry at different baffle gaps and various flow rates - FEYZİOĞLU, AHMET (My University, 2023)
The effects of changing 90 mm and 110 mm plate spacings and FR factor of 0.9 kg/h, 1.3 kg/h, 1.7 kg/h, 1.9 kg/h on the total heat transfer performance and PD in the new design HX were examined. The results obtained by taking into account the change in plate spacing and FR factor of 0.9 kg/h, 1.3 kg/h, 1.7 kg/h and 1.9 kg/h, as well as variable factors, were transferred to the study and displayed in figures. In the study, firstly, the results of HCO obtained by changing FR and range were monitored. In the analysis, the interval values were 90 mm and 110 mm and the changes in the FR values of 0.9 kg/h, 1.3 kg/h, 1.7 kg/h and 1.9 kg/h increased in direct proportion. The smallest value of the heat transfer rate was obtained at 110 mm plate spacing and 0.9 kg/h FR. In addition, if the plate spacing was 90 mm, the smallest HCO was obtained at 0.9 kg/h. The largest HCO was obtained when the plate spacing was 90 mm and FR was 1.9 kg/h. In the second part of the study, the results of PD obtained by changing FR and gap were monitored. In the analysis, the interval values were 90 mm and 110 mm and the changes in FR values of 0.9 kg/h, 1.3 kg/h, 1.7 kg/h and 1.9 kg/h increased in direct proportion. The smallest value of PD level was obtained at 90 mm plate spacing and 0.9 kg/h FR. In addition, if the plate spacing was 110 mm, the smallest heat transfer coefficient was obtained at 0.9 kg/h. The largest PD value was obtained when the plate spacing was 110 mm and FR was 1.9 kg/h. In the last part of the study, the results obtained by changing FR and range of the HTPD value were monitored. In the analysis, the interval values were 90 mm and 110 mm, and the changes in FR values of 0.9 kg/h, 1.3 kg/h, 1.7 kg/h and 1.9 kg/h decreased in direct proportion. The smallest value of the HTPD level was obtained at 110 mm plate spacing and 1.9 kg/h FR. In addition, if the plate spacing was 90 mm, the smallest HTPD value was obtained at 1.9 kg/h. The highest HTPD value was obtained when the plate spacing was 90 mm and FR was 0.9 kg/h. Therefore, choosing a system with a 90 mm plate spacing and a FR of 0.9 kg/h will be more efficient in terms of thermohydraulic performance and pressure balancing. As a result, it was concluded that if the plate spacing was selected as 90 mm, a 15 % improvement could be achieved compared to the system design with a 110 mm plate spacing. As a new, it is thought that it will contribute to the literature in future studies, as the thermal performance, pressure drop and heat transfer coefficient results obtained at new flow rate values and compartment spacing values are obtained for the first time in a new STH designed in different dimensions than the literature.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Exchanger; Baffle board; CFD; Computational